Implementasi Kebijakan Pemerintah Kota Surabaya Terhadap Sekolah Arek Suroboyo (SAS) di SDN Simokerto 1-134 Surabaya - Nia Eka Safitri; Anggraeny Puspaningtyas (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
One of the policies implemented by the Surabaya city education office is the Arek Suroboyo School program which is often nicknamed SAS. The Arek Suroboyo School Program is a type of program that has freedom to learn, both freedom for teachers to express their creativity and freedom for students when receiving learning. To find out whether this program has an influence or not in the world of education, we need to implement it. This research aims to determine the results of the implementation of the Arek Suroboyo School (SAS) program at the Simokerto 1-134 Surabaya State Elementary School, whether the school is able to create a school environment that can shape student character, hone creativity and active knowledge of students with comfortable and comfortable learning. pleasant. This research uses descriptive qualitative research with data collection techniques through observation, literature study, and interviews with several stakeholders at SDN Simokerto 1-134 Surabaya which is currently running the Arek Suroboyo School (SAS) program. The implementation carried out at SDN Simokerto 1-134 Surabaya is already underway with various activities to support the Arek Suroboyo School (SAS) program.